ERAP1 and ankylosing spondylitis. - Keidel, S; Chen, L; Pointon, J; Wordsworth, B (2013)
The strong genetic association of ERAP1 (endoplasmic reticulum aminopeptidase 1) with ankylosing spondylitis (AS), which is restricted to HLA-B27 positive cases, has profound pathogenetic implications. ERAP1 is involved in trimming peptides to optimal length for binding to HLA class 1 molecules, thereby not only affecting the stability and processing of HLA-B27 but also influencing the peptide repertoire presented to the immune system. This could have secondary effects on specific adaptive or autoimmune responses in AS. However, it appears increasingly likely that the pathogenic effect of ERAP1 may be mediated through effects on innate immunity, such as altering the interaction between HLA-B27 and immune receptors such as the killer immunoglobulin-like receptors (KIR) found on a range of innate immune cells or via the endoplasmic reticulum unfolded protein response. ERAP1 variants associated with reduced endopeptidase activity appear to be protective against AS, raising the possibility that ERAP1 inhibition could represent a future treatment strategy.